Movimentos sociais na era da internet: uma leitura comparativa da ação política nos protestos das Jornadas de Junho, no Brasil, dos Indignados, na Espanha, e do Occupy Wall Street, nos EUA - Braga, Julio Trevisam (2016)
Amid the current repercussion around world of protests raised in criticism to a progressive loss of State autonomy in face of the regulation of profit by financial speculation, among the social movements of the present day it’s perceived the reappropriation of principles such as autonomy, horizontality, independence and solidarity. At the same time, it was highlighted among this movements the approach of action methodologies based on the instrumentalization of cyberculture. This context gives us the opportunity to reopen the debate about the historian’s treatment of the problematics of a history of the present time. On that intent, what discursive and instrumental elements are arranged between movements such Occupy Wall Street and the NYC General Assembly, in the USA, Democracia Real YA! platform, in Spain, Movimento Passe Livre – SP and the ANEL and Juntos! collectivies, which can confirm the proposal for a new model of political participation, linked to the perception of a demand for another city and another democracy? Finally, what’s the intensity evidenced in the respective protests about the interaction of urban space occupation and the use of digital networks? For the analyses, we exclusively investigate the blogs of each movement. Our considerations pointed out that, among them, these principles present different tonalities of familiarization, affirming, therefore, different practices of action and specific conceptions around the model of political participation idealized by each movement